Meningkatkan Hasil Belajar Menendang (Shooting) Sepak Bola Melalui Modifikasi Latihan Target - Kristian Pratiko, Lindon; Razali; Iqbal, Muhammad (INSPIREE: Indonesian Sport Innovation Review, 2021)
The  purpose  of   the  study. In improving the learning outcomes of shooting in Football games through modification of target exercises for fourth grade students of SDS KARTIKA VIII-2 semester in the 2019/2020 school year. Materials and methods. classroom action research that follows the model of Kemmis and Taggart theory. This study includes 2 cycles where each cycle includes 4 stages, namely planning (planning), acting (implementation), observing (observing), reflecting (reflection). research subjects were 25 students, while data were collected through tests and observations. Results. The results of the study showed that there was a significant increase in learning outcomes for fourth grade students. This is evidenced by the percentage of fourth grade students who achieve the KKM scores on the Shooting test in a football game in each cycle. In the first cycle = 64%; cycle II = 88%, with the result that the percentage is proven in the first cycle to the second cycle has increased by 24%. Conclusions. Shooting in football games through target practice modification can improve students' shooting skills.